Development of Self-Regulation in Adolescents in the Context of Educational Process - Popova, S.I. (Psihologičeskaâ nauka i obrazovanie, 2017)
The paper reviews the issue of self-regulation development in adolescents as the process of supporting favourable and transforming unfavourable emotional states appropriate to the performed joint activity. Experiencing intense emotions makes personal growth more difficult for the adolescent, and therefore the task of promoting self-regulation becomes extremely important. Our hypothesis was that the development of self-regulation contributes to the adolescent’s ability to recognize and interpret emotional states and extends the range of practices available to him/ her. Creating operative images of an object in concrete situations has a mediated effect on the transformation of the emotional states experienced by the adolescent. The revealed social psychological conditions were implemented through role-based forms of group activities, methods and means of self-regulation development. We evaluate the effectiveness of the development of self-regulation in adolescents based on certain criteria and analyse the outcomes of an experimental study. The ideas proposed in this paper can be used in the formation of regulative universal learning actions in adolescents at school to develop their ability to consciously regulate emotional states in the context of implementing the federal state education standards. Проблема развития способности подростка к саморегуляции представлена как процесс поддержки благоприятных и преобразования неблагоприятных эмоциональных состояний, адекватных выстраиваемой совместной деятельности. Обращается внимание на то, что поскольку проживание учащимся интенсивных эмоциональных состояний препятствует его личностному становлению, задача развития саморегуляции является особенно актуальной. Проверялось предположение о том, что развитие саморегуляции способствует овладению подростком способностями распознавать и интерпретировать эмоциональные состояния, расширению спектра используемых им способов. Утверждается, что создание подростком оперативных образов объекта в конкретной ситуации оказывает опосредованное влияние на преобразование проживаемых им эмоциональных состояний. Выявленные психолого-педагогические условия реализовывались в социально-ролевых формах групповой деятельности, методах и средствах развития саморегуляции. На основе выделенных критериев оценивается эффективность развития способности подростка к саморегуляции, анализируются результаты опытно-экспериментальной работы. Делается вывод о том, что идеи, представленные в статье, могут быть использованы при формировании регулятивных универсальных учебных действий с позиций развития у школьника способности произвольно и осознанно регулировать эмоциональные состояния в условиях реализации ФГОС основного общего образования.